Vulnerability of long-term memory to temporal delays in amphibians - Puddington, Martin Miguel (2013)
Two experiments with toads were designed to test the hypothesis that extinction (i.e., nonreinforced) performance is a function of time since the last reinforced trial (the memory-decay hypothesis). in experiment 1, groups of toads (rhinella arenarum, formerly bufo arenarum) received 15 daily acquisition trials each reinforced with access to water during 300 s in a runway. after the last acquisition trial, animals were assigned to one of 6 retention intervals: 1, 4, 8, 16, 32, and 64 days. extinction started after the retention interval and lasted 8 additional daily trials. overall extinction performance was a logarithmic function of the length of the retention interval. in experiment 2, two groups of toads received 15 daily acquisition trials each reinforced with access to water in a runway for either 30 or 600 s, thus producing two reward magnitudes. after an 8-day retention interval, the extinction performance in 8 additional daily trials was weaker after training with the small, than with the large reward magnitude. these results support a memory-decay hypothesis and suggest that the instrumental performance of toads is strongly influenced by the time since the last reinforced trial.